The Urgency of Applying Technology to Guidance and Counseling Services - Aprilia Sari Yudha; Dwiky Fajri Al Giffary; Rofiqoh Rosidi (Universitas Islam Cordoba Banyuwangi, 2025)
Guidance and counseling is an important component in maintaining individual mental and emotional health. This service provides psychological support, direction, and problem solving to individuals experiencing emotional difficulties, interpersonal conflicts, developmental issues, or other challenges in their lives. Technology is the result of the development of science, which occurs in the world of education. Therefore, it is appropriate that education itself also utilizes technology. One of the urgency of applying technology in guidance and counseling services is the increasing need for accessibility. The purpose of this research is 1. To find out what technology can help the Guidance and Counseling service process. 2. To know the urgency of implementing technology in services and counseling. The method used is a descriptive qualitative approach through research literature. The results of this study are also important to note that technology can improve the quality of guidance and counseling services. With an online platform, counselors can provide supporting resources such as articles, videos, or self-evaluation tools that assist clients in self-understanding and problem-solving processes.